PENGARUH OPINI AUDIT, UKURAN PERUSAHAAN DAN PROFITABILITAS TERHADAP AUDIT DELAY PADA PERUSAHAAN BATU BARA - Ayni Bilqis Hanifah; Sefti Cahyani Triwulandari; Emy Silvia Putri; Dwi Ermayanti Susilo (Politeknik Bisnis Indonesia, 2023)
This study aims to determine how the audit opinion, company size, and profitability affect audit delay in coal companies listed on the Indonesian stock exchange. This study employs quantitative research techniques. Coal businesses registered on the Indonesia Stock Exchange for the years 2021–2022 make up the sample population. Purposive sampling is a sample selection technique used in this study, with a total sample of 19 coal companies. The chosen analytical method is multiple regression analysis using SPSS 26 statistical software. The data taken is secondary data obtained from the IDX website: www.idx.co.id. The results of this study indicate that audit opinion has a significant positive effect on audit delay in coal companies, while company size and profitability have no effect on audit delay in coal companies.